Genomes of 12 fig wasps provide insights into the adaptation of pollinators to fig syconia. (20th March 2021) - Xiao, Jinhua; Wei, Xianqin; Zhou, Yi; Xin, Zhaozhe; Miao, Yunheng; Hou, Hongxia; Li, Jiaxing; Zhao, Dan; Liu, Jing; Chen, Rui; Niu, Liming; Ma, Guangchang; et al.
Abstract: Figs and fig pollinators are one of the few classic textbook examples of obligate pollination mutualism. The specific dependence of fig pollinators on the relatively safe living environment with sufficient food sources in the enclosed fig syconia implies that they are vulnerable to habitat changes. However, there is still no extensive genomic evidence to reveal the evolutionary footprint of this long-term mutually beneficial symbiosis in fig pollinators. In fig syconia, there are also non-pollinator species. The non-pollinator species differ in their evolutionary and life histories from pollinators. We conducted comparative analyses on 11 newly sequenced fig wasp genomes and one previously published genome. The pollinators colonized the figs approximately 66.9 million years ago, consistent with the origin of host figs. Compared with non-pollinators, many more genes in pollinators were subject to relaxed selection. Seven genes were absent in pollinators in response to environmental stress and immune activation. Pollinators had more streamlined gene repertoires in the innate immune system, chemosensory toolbox, and detoxification system. Our results provide genomic evidence for the differentiation between pollinators and nonpollinators. The data suggest that owing to the long-term adaptation to the fig, some genes related to functions no longer required are absent in pollinators.